PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN SAHAM PUBLIK, UMUR PERUSAHAAN, DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS DENGAN JUMLAH BENCANA ALAM SEBAGAI MODERASI - Mohammad Ali (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The purpose of this study was to obtain empirical evidence about the effect of institutional ownership, public share ownership, company age, and company size on profitability with natural disasters as moderating food and beverage industry companies. The design of this study uses quantitative methods with types of explanatory research. This study uses secondary data in the form of annual financial reports for 2012 to 2017. Sampling is done by purposive sampling method so that a set of 19 companies as research samples with observation total 114. The results showed that institutional ownership, share ownership and company age had a positive effect on profitability, while company size did not affect profitability. Research also shows that natural disasters strengthen the influence of institutional ownership, public share ownership, company age and company size on company profitability.